Two fluoroquinolones and their combinations with hyaluronan: comparison of effects on canine chondrocyte culture - P. Siengdee (2018)
© 2016 John Wiley & Sons Ltd Fluoroquinolones (FQs) are frequently used for septic arthritis. Increased antibacterial activity has been associated with mammalian cell cytotoxicity that may increase the risk of developing osteoarthritis. This study compared the direct effects of two different FQs, enrofloxacin (Enro) and marbofloxacin (Mar), on normal primary canine chondrocytes and inflammatory-stimulated chondrocytes, in addition to their administration in combination with hyaluronan (HA). Cell viability, cell apoptosis, s-GAG production, and expression patterns of inflammatory, extracellular matrix (ECM) component and protease genes were measured. Enro co-culturing with HA could modify s-GAG synthesis compared with the negative control group. Co-treatment with both FQs and HA significantly decreased cell viability and induced more total apoptotic cell death compared with the negative control and pre-IL-1β-stimulated group. Enro regulated IL-1β-stimulated cells to overexpress IL-1β, TNF, and MMP3, whereas Mar induced upregulation of PTGS2 and NFKB1 and enhanced the expression of ECM component genes HAS1, COL2A1, and ACAN as well as TIMP1 and MMP9. Simultaneous use of HA with Enro can effectively reduce the expression of IL-1β, TNF, and MMP3 in pre-IL-1β-stimulated chondrocytes. These results suggest the beneficial effects of HA in reducing the adverse effects of Enro treatment at the transcriptional level.